Analysis of Clinical Characteristics and Risk Factors of Severe Adenovirus Pneumonia in Children - Zhong, Haiqin; Dong, Xiaoyan (Frontiers in Pediatrics, 2021)
Objective: To analyze the clinical characteristics of adenovirus pneumonia (ADVP) in children and explore risk factors for severe ADVP. Methods: Clinical data from 7008 hospitalized children with community-acquired pneumonia and 211 with ADVP were retrospectively analyzed between July 2014 and June 2019. Eighty-six patients were diagnosed with severe pneumonia, and related risk factors were analyzed. Results: ADVP accounts for 3.01% (211/7008) of CAP in hospitalized children. Among 211 patients, 167 (64.9%) children aged 1 to 5 years old, and the onset was in winter and spring for 126 (59.7%) children. All patients had cough, and 116 (92.8%) patients with mild cases and 82 (95.4%) patients with severe cases had varying degrees of fever. The duration of fever in the severe ADVP group and mild ADVP group was 7.3 d and 5.4 d, respectively. The average hospital stays were 9.8 d and 5.8 d, respectively. There was no significant difference in the levels of WBC and ESR between the two groups, but the levels of N%, CRP, PCT and LDH in children with severe ADVP were significantly higher than those in the mild ADVP group. The univariate analysis showed that there were significant differences between the severe ADVP group and the mild ADVP group in ≥7 days of fever and high IgE (P<0.05). There was no significant difference in sex, age, onset season, mycoplasma infection, bacterial infection between the two groups (P>0.05). The multivariate logistic analysis showed that ≥7 days of fever and high IgE were independent risk factors for severe ADVP (P<0.05). Conclusions: Children with severe ADVP have long fever duration, a strong inflammatory response and immune function disturbance. Fever duration (≥7 days) and high IgE were independent risk factors for severe ADVP.